WEB-BASED DESIGN OF DHARMA WANITA ASSOCIATION (DWP) LPKA CLASS II JAKARTA FINANCIAL REPORT APPLICATION - Fenina Adline Twince Tobing; Eunike Endariahna Surbakti; Marlinda Vasty Overbeek (Jurnal Sinergitas PKM & CSR, 2022)
Lembaga Pembinaan Khusus Anak (LPKA)Class II Jakarta, there is a Dharma Wanita Association (DWP) Jakarta Class II LPKA organization whose members are all the wives of civil servants and also female civil servants who serve in that place. One of the keys to the success of an organization is being able to manage finances well, one of which is reflected in routinely making financial reports every month. Not only important for large companies, financial reports that are compiled and updated regularly are also important for MSME businesses, online businesses or organizations. It doesn't matter if someone doesn't have an educational background in accounting, but is still able to make complete financial reports.Technological advances encourage DWP LPKA Class II Jakarta to be able to carry out their work in terms of financial reporting to make it easier and more efficient by using applications that we have researched and implemented through the Multimedia Nusantara University (UMN) Community Service Program (PKM) in 2022 and DWP LPKA Class II Jakarta members received this form of community service with great enthusiasm. Through this PKM activity it is hoped that there will be an increase in the application of science and technology in society (mechanisms, IT, management) and for improving community values from a social and financial management perspectiveabstract in bahasaLembaga Pembinaan Khusus Anak (LPKA) Kelas II Jakarta, terdapat organisasi Dharma Wanita Persatuan (DWP) LPKA Kelas II Jakarta yang beranggotakan seluruh Istri PNS dan juga PNS wanita yang bertugas di tempat tersebut. Salah satu kunci sukses sebuah organisasi adalah mampu mengelola keuangan dengan baik, salah satunya tercermin dari rutin membuat laporan keuangan setiap bulan. Tidak hanya penting bagi perusahaan besar, laporan keuangan yang disusun dan diperbaharui secara berkala juga penting dilakukan oleh bisnis UMKM, usaha online atau organisasi. Tidak masalah jika seseorang tidak memiliki latar belakang pendidikan akuntansi, namun tetap mampu membuat laporan keuangan yang lengkap.Kemajuan Teknologi mendorong untuk membantu DWP LPKA Kelas II Jakarta untuk dapat melaksanaan pekerjaan mereka dalam hal pelaporan keuangan agar lebih mudah dan efisien dengan menggunakan aplikasi yang telah kami teliti dan kami implementasikan melalui Program Pengabdian Kepada Masyarakat (PKM) Universitas Multimedia Nusantara (UMN) tahun 2022 dan anggota DWP LPKA Kelas II Jakarta memerima bentuk pengabdian masyarakat yang kami lakukan dengan sangat antusias. Melalui kegiatan PKM ini diharapkan adanya peningkatan penerapan IPTEK di masyarakat (mekanisme, IT, manajemen) dan untuk perbaikan tata nilai masyarakat dari segi sosial dan manajeme keuangan.